2020
DOI: 10.1016/j.clgc.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Cancer-specific Survival After Neoadjuvant Chemotherapy and Radical Cystectomy in Patients With Bladder Cancer and Squamous Cell Variant: A Multi-institutional Study

Abstract: Background: Non-urothelial carcinoma (UC) malignancies are traditionally considered to yield a more aggressive clinical course and little is known about their response to neoadjuvant therapy. We examined the effect of neoadjuvant chemotherapy (NAC) on a large population of bladder cancer (BCa) patients with histological variant (HV). Methods:We relied on aretrospective, multicentre database including 2,858 patients with BCa, who received radical cystectomy (RC) +/− NAC, between 1990 and 2017. Pure and mixed HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Interestingly, the finding that luminal-like subtypes are more responsive than basal are in line with what is known on the response of histologic variants of MIBC. Micropapillary tumors are luminal-like [ 69 ] and have been described to have a good response to NAC [ 70 , 71 ], whereas squamous-cell carcinoma of the bladder has a poor response to NAC [ 72 , 73 , 74 , 75 ]. One interpretation of histologic variants is that they represent extreme forms of the various differentiation states of urothelial carcinoma captured by molecular subtypes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the finding that luminal-like subtypes are more responsive than basal are in line with what is known on the response of histologic variants of MIBC. Micropapillary tumors are luminal-like [ 69 ] and have been described to have a good response to NAC [ 70 , 71 ], whereas squamous-cell carcinoma of the bladder has a poor response to NAC [ 72 , 73 , 74 , 75 ]. One interpretation of histologic variants is that they represent extreme forms of the various differentiation states of urothelial carcinoma captured by molecular subtypes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,12 In the setting of MIBC, however, reports and opinions conflict regarding the benefit of NAC. 6,11,12,[15][16][17] In a review of 2,018 patients with nonPUC histology from the National Cancer Database Vetterlein et al found that although NAC decreased the frequency of nonorgan confined disease at the time of cystectomy in micropapillary bladder cancer cases, this did not translate into a survival benefit. 15 However, in a series of 82 patients from Memorial Sloan Kettering Cancer Center down staging to pT0 occurred in 45% of patients who received NAC compared to 13% who did not, and patients with pT0 disease had higher OS rates (92% vs 25%) and lower rates of recurrence (21% vs 79%) at 24-month followup.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,14 In cases with heterogeneous histology comprised of both urothelial and nonurothelial components the limited availability of comparative data and conflicting results of existing studies pose an opportunity to better define the effectiveness of NAC and cystectomy. 6,11,12,[15][16][17] To address this clinical question, we compared chemotherapy response as measured by pathological down staging and survival outcomes among bladder cancers with nonPUC histology treated with either NAC followed by cystectomy or cystectomy alone.…”
mentioning
confidence: 99%
“…Micropapillary morphology in solid malignancies is known to have a distinct propensity for lymphovascular invasion, which can lead to a higher rate of LNI compared with the non-micropapillary histological variants [29,30]. Therefore, these observations suggest the need for further studies involving an accurate analysis of the biological, pathological, and clinical factors of the urothelial and non-urothelial bladder cancer variants 16 (88.9) 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) 2 (11.1) to define the best multidisciplinary (surgery, radiation therapy, chemotherapy, and innovative treatment strategies) approach for each histological subtype, with a particular emphasis on immunotherapy and targeted therapies [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%